Returning ISIS fighters : what should be done with them? - Cheong, Damien D. (2015)
Reports that several disillusioned ISIS fighters want to return to their home countries pose a serious challenge of developing an effective response. Their governments will have to strike a careful balance between deterrence, rehabilitation, intelligence-gathering needs and cost effectiveness.